Razvoj odnosa izmedu EZ-a i država srednje i istočne Europe - Pavlović, Čedomir (Promet - Traffic&Transportation, 2012)
Market makes an indispensable element of the development of democratic states. In the EC the internal transport market has already been structured, however there are a variety of unresolved issued. The economies of the nations of Central and East Europe must necessarily undergo restructuring, within the scope of European integration processes which then particularly refers to traffic. This makes an absolute prerequisite for a more comprehensive arrangement of relationships with the EC and its member states in this segment.